Pengaruh Financial Literacy, Self-control Terhadap Pengelolaan Keuangan - Prameswari, Axanda Bilqis; Yuhertiana, Indrawati (Gorontalo Accounting Journal, 2025)
This study aimed to analyze the effect of financial literacy and self-control on the financial management of early career women in Surabaya. A quantitative approach was applied using a survey method through questionnaires distributed to 145 respondents, who were accounting graduates from public universities in Surabaya. Data were analyzed using SmartPLS 4.0 with the Structural Equation Modeling (SEM) approach. The results revealed that financial literacy and self-control had a positive and significant effect on financial management. These findings indicate that higher financial literacy is associated with better budgeting and wiser financial decision-making. Furthermore, self-control helps early career women avoid impulsive spending triggered by workplace lifestyle pressures. This study was limited to a single city and profession, so the findings cannot yet be generalized. Nonetheless, it provides an original contribution by highlighting the combined importance of financial literacy and self-control among young professional women.